2015
DOI: 10.1016/j.jdent.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and protein-repellent orthodontic cement to combat biofilms and white spot lesions

Abstract: Objectives White spot lesions are the most undesired side-effect of fixed orthodontic treatments. The objectives of this study were to combine nanoparticles of silver (NAg) with 2-methacryloyloxyethyl phosphorylcholine (MPC) to develop a modified resin-modified glass ionomer cement (RMGI) as orthodontic cement with double benefits of antibacterial and protein-repellent capabilities for the first time. Methods NAg and MPC were incorporated into a commercial RMGI. Another commercial orthodontic adhesive also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 55 publications
(155 reference statements)
0
53
0
Order By: Relevance
“…An occlusogingival load was applied at a cross-head speed of 0.5 mm/min until the bracket detached. Orthodontic bracket shear bond strength = load at failure/bracket surface area3839.…”
Section: Methodsmentioning
confidence: 99%
“…An occlusogingival load was applied at a cross-head speed of 0.5 mm/min until the bracket detached. Orthodontic bracket shear bond strength = load at failure/bracket surface area3839.…”
Section: Methodsmentioning
confidence: 99%
“…The reason for this great reduction in biofilm viability is likely that the MPC reduced the protein adsorption on the material, hence there was less protein attachment and more direct material-bacterial contact, thus enhancing the contactinhibition of DMAHDM. In addition, previous studies showed that MPC could repel protein adsorption, but it did not kill the bacteria 15,24,25) . Therefore, after MPC had repelled the majority of bacteria attachment, the DMAHDM in AEO would kill the rest of the bacteria 6 Dent Mater J 2018; : -that still attached to the AEO.…”
Section: Discussionmentioning
confidence: 98%
“…The samples were then sterilized with ethylene oxide (Anprolene AN 74i, Andersen, Haw River, NC, USA) and de-gassed for 3 days following the manufacturer's instructions 18,27) . A micro bicinchoninic acid (BCA) method was applied to measure protein adsorption 23,24) . Each disk was stored in phosphate buffered saline (PBS) for 2 h after being soaking in bovine serum albumin (BSA) (Sigma-Aldrich) solution at 37°C for 2 h. The protein solution had BSA at a concentration of 4.5 g/L, following a previous study 23) .…”
Section: Protein Adsorption On Self-etch Adhesive Surfacementioning
confidence: 99%
See 2 more Smart Citations